Dynamic response of airport concrete pavement to impact loading - Cai, Jing (2013)
The pavement-subgrade interaction is an important issue in the concrete pavement design.The present study focuses on the analysis of the dynamic deflection and the velocity response of airport concrete pavements to impact loading. The pavement-subgrade interaction is simplified as a linear viscoelastic model, in which the subgrade is composed of two layers (a base layer and a soil layer). The subgrade’s synthetical modulus and damping coefficient are obtained by the method of weighed mean. Through the Fourier and the Laplace transform the solution of the equilibrium equation of the pavement-subgrade system is deduced and the dynamic deflection solution of the pavement-subgrade system is obtained. In this study, an impact aircraft landing load increasing proportional to the aircraft vertical landing acceleration is considered. A Matlab program is compiled based on the solution to assess the influence of various system parameters (slab thickness h, slab size, subgrade reaction modulus Ks and subgrade damping factor C0) on the dynamic deflections of the pavement slab. The influence of h and Ks on the dynamic velocity response of the slab is also discussed. The results show that changing the damping factor and the subgrade reaction modulus has only a small influence on the deflection of the slab and the deflection, while the amplitude of velocity response and the frequency of velocity responses all decrease with the increase of the slab thickness. If the pavement slab size is decreased, the deflection at the center of the slab will decrease. A nonlinear relationship can be established between h and the maximum deflection, while linear relationships exist between C0 and the maximum deflection, as well as Ks and the maximum deflection.